Efficient joint channel equalization and tracking for V2X communications using SC-FDE schemes - Pedrosa, Pedro (2020)
Our aim with this paper is to present a solution suitable for vehicle-to-everything (V2X) communications, particularly, when employing single-carrier modulations combined with frequency-domain equalization (SC-FDE). In fact, we consider the V2X channel to be doubly-selective, where the variation of the channel in time is due to the presence of a Doppler term. Accordingly, the equalization procedure is dealt by a low-complexity iterative frequency-domain equalizer based on the iterative block decisionfeedback equalization (IB-DFE) while the tracking procedure is conducted employing an extended Kalman filter (EKF). The proposed system is very efficient since it allows a very low density of training symbols, even for fast-varying channels. Furthermore only two training symbols are required to initialize the tracking procedure. Thus, ensuring low latency together with reduced channel estimation overheads.